Jaden Easton

2021-08-16

To simplify the given equation for m.

An equation is given as$y=mx+b$ .

An equation is given as

odgovoreh

Skilled2021-08-17Added 107 answers

Calculation:

We have given as equation as$y=mx+b$ .

We will do some basic mathematical operation and solve the given equation.

Now let us simplify given equation.

$y=mx+b$

$\Rightarrow y-b=mx+b-b$ [Substrating b from both sides]

$\Rightarrow y-b=mx$ [Simplifying]

$\Rightarrow \frac{y-b}{x}=\frac{mx}{x}$ [Dividing both side by x]

$\Rightarrow m=\frac{y-b}{x}$ [Simplifying]

Hence, we can say that solution for given equation will be$m=\frac{y-b}{x}$ .

We have given as equation as

We will do some basic mathematical operation and solve the given equation.

Now let us simplify given equation.

Hence, we can say that solution for given equation will be

Jeffrey Jordon

Expert2021-12-20Added 2575 answers

Answer is given below (on video)